The Nature of Knowledge and Epistemic Interests of Radiography Science—An Analysis of Doctoral Dissertations Using Critical Normative Epistemology Framework - Törnroos, Sanna; Leino‐Kilpi, Helena; Siekkinen, Mervi; Metsälä, Eija (Wiley, 2026)
Background and aim: Radiography science is a health sciences discipline and a knowledge system focusing on research into medical imaging and radiation therapy-related phenomena: patient care, technology, safety and quality in these environments. This study aims to understand the nature of knowledge in radiography research by investigating epistemic interests and knowledge types.
Methodological design: The study used nursing science critical normative epistemology as a framework for the analysis. We used document analysis as a method, and the selected documents for the study were dissertations from the field of radiography between the years 1998 and 2020. The data corpus consisted of the methodology section of the dissertations and the study's aim and purpose. Data was analysed with an abductive analysis approach.
Findings: The findings of the study indicate that radiography research has a dedicated type of knowledge according to epistemic interest. Knowledge is acquired through varying methodologies, and there does not seem to be any typical radiography methodology used, even though some methods are more common than others. According to our study, epistemic interests in radiography science are, in the majority of cases, inferential, that is, they aim to explain and explore phenomena within the domain of medical imaging and radiation therapy. However, there are also referential studies, aiming to understand different actors, processes and caring actions involved in the practice of this domain. Radiography research also furthers transformative interests, such as transformation focused on suppressed groups or practices in need of critical reflection. To a lesser extent, radiography research seems to further normative interests.
Conclusions: Pragmatism describes the nature of radiography knowledge. The different knowledge types generated indicate a need for generalisable knowledge and subjective knowledge, as well as further critical reflection on the current practices in diagnostic imaging and radiotherapy.